Artificial milk-feeding women׳s views of their feeding choice in Ireland. Issue 6 (June 2015) - Carroll, Margaret; Gallagher, Louise; Clarke, Mike; Millar, Sally; Begley, Cecily
Abstract Objective despite the well-documented benefits of breast feeding to both mother and child, breast-feeding initiation rates in Ireland are the second lowest in Europe. This study set out to explore the views of women from low socio-economic groups in Ireland on their choice to feed their infants artificial milk, and to elicit factors that may encourage these women to breast feed in the future. Design a qualitative descriptive approach was used. Methods data were collected through recorded focus groups and individual interviews, using a semi-structured interview schedule. Data were transcribed verbatim. Setting interviews took place in two regions in the Republic of Ireland, north and south. Participants a purposive sample was drawn from the population of 2572 women taking part in the Irish Infant Feeding Study who had never breast fed previously, had intended to, and had, fed this infant artificial milk and who had completed their education before they were 18 years of age. Two focus groups with two women in each were conducted and six women took part in individual interviews. Analysis constant comparative analysis was performed to construct the categories and concepts that led to the final themes. Findings these artificial milk-feeding women based their infant feeding decision on many social and experiential factors. The major influences on their decisions were: personal attitudes toward feeding methods, and external influences on infant feeding methods. Attitudes towards other women and feeding future infants reinforced a strong preference towards artificial milk feeding. Key conclusions and implications for practice it is apparent that a prevailing culture that is unreceptive to breast feeding and the lack of positive breast-feeding role models, contributed to a strong commitment to artificial milk feeding for these participants. Promotion of breast feeding must take account of the complex contexts in which women make decisions. Advice regarding breast feeding should take account of women׳s feelings and avoid undue pressure, while still promoting the benefits of breast feeding to women and their families.